Magnetic conjugated polymer nanoparticles doped with a europium complex for biomedical imaging. Issue 6 (21st May 2018) - Kemal, E.; Peters, R.; Bourke, S.; Fairclough, S.; Bergstrom-Mann, P.; Owen, D. M.; Sandiford, L.; Dailey, L. A.; Green, M.
Abstract : Self-assembling conjugated polymer nanoparticles containing PVK and PLGA-PEG as a matrix polymer were doped with both a luminescent rare-earth complex and magnetic nanoparticles (SPIONs), giving rise to materials that are both luminescent and magnetic. Abstract : Self-assembling conjugated polymer nanoparticles containing PVK and PLGA-PEG as a matrix polymer were doped with both a luminescent rare-earth complex and magnetic nanoparticles (SPIONs), giving rise to materials that are both luminescent and magnetic. Nanoparticle sizes ranged from 80–110 nm without SPIONs and showed an increase in size (200–1000 nm) with additional SPION content (11–54%). Quantum yields (QYs) of 24% and 18% were measured for systems without and with 11% SPIONs, respectively. Optical properties were stable and suitable for biological imaging applications.